2009
DOI: 10.4323/rjlm.2009.101
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional considerations on the atrioventricular node arterial vascularization

Abstract: The atrioventricular node (AVN) is the relay station for electrical impulses passing from the atria to the ventricles. The arterial resources of the AVN are functionally relevant and may be interfered by various surgical procedures which deal with the cardiac valves. Our study aim to bring detailed evidences on the arterial supply of the AVN. We dissected and microdissected 50 human adult hearts without any known history or evident cardiac pathology, in order to evidence the arterial suppliers of the AVN; sube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The AVNb is most often a branch of the right coronary artery in approximately 90% of cases entering into the triangle of Koch [ 20 , 21 ]. In some cases, the AVNb is a terminal branch of the LCxA, and in others, both coronary arteries supply the AV node [ 22 ]. For the origin of the AVNb, we classified our specimens as AVNb originating from the RCA proximal to the IVb (type I), AVNb originating from the junction of the RCA and IVb (type II), AVNb originating from the RCA distal to the IVb (type III), AVNb originating from the IVb (type IV), and AVNb originating from the LCxA (type V) [ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AVNb is most often a branch of the right coronary artery in approximately 90% of cases entering into the triangle of Koch [ 20 , 21 ]. In some cases, the AVNb is a terminal branch of the LCxA, and in others, both coronary arteries supply the AV node [ 22 ]. For the origin of the AVNb, we classified our specimens as AVNb originating from the RCA proximal to the IVb (type I), AVNb originating from the junction of the RCA and IVb (type II), AVNb originating from the RCA distal to the IVb (type III), AVNb originating from the IVb (type IV), and AVNb originating from the LCxA (type V) [ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AVNb originated from the RCA distal to the IVb in approximately 65% of our specimens (type III). The anatomical importance of the left AVNb is also important in, for example, surgical manipulation of the right fibrous ring [ 22 , 28 ]. Damage to the AV node and/or the AVNb has been shown to produce pathological conditions related to the pacing of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The dual arterial supply should be highly noted due to its rare occurrence, which was also mentioned in the study performed by Kazemisaeid et al (2012), detecting dual‐supply in 0.01% of subjects studied. In regards to morphological patterns of the AVNA, Rusu et al (2009) reported five different patterns found via dissections of 50 hearts. The discovered patterns in Rusu et al study were type 1 in 22% (AVNA originated from U‐shape turn of RCA), type 2 in 18% (AVNA originated from the IIVA), type 3 in 34% (AVNA originated from the left RVA), type 4 in 8% (AVNA originated from trifurcation of RCA), and type 5 in 18% (AVNA originated from the circumflex artery).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 5028 articles were initially evaluated by two independent reviewers. Eventually, 33 articles met the required criteria and were used in this meta‐analysis (James & Burch, 1958; Romhilt et al, 1968; Vieweg et al, 1975, 1982; Hutchinson, 1978; Anderson & Murphy, 1983; Brugada et al, 1990; Wang et al, 1990; Sneddon et al, 1991; Burke et al, 1993; Krupa, 1993; Sow et al, 1996; Arid et al, 2000; Lin, 2000; Sanchez‐Quintana et al, 2001; Futami et al, 2003; Kaplana, 2003; Berdajs et al, 2008; Pejković et al, 2008; Saremi et al, 2008; Nerantzis et al, 2009; Paulsen & Vetner, 2009; Ramanathan et al, 2009; Rusu et al, 2009; Ballesteros et al, 2010; El‐Maasarany et al, 2010; Cezlan et al, 2012; Kazemisaeid et al, 2012; Sabnis & Silotry, 2012; Verma et al, 2014; Divyaprakash et al, 2016; Kawashima & Sato, 2018; Iwanaga et al, 2023). The overall data collection process can be found in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation